Analysis of financial data on the time series using data from the stock market - Shachcha, Ifad Bhuiyan; Siam, Muhammad Ziaus (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.